Analisis Pembentukan Portofolio Optimal dengan Single Index Model dan Z-Score pada Emiten IDX BUMN 2O - Avianti, Jihan; Ratnasari, Martdian (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2021)
This study aims to form an optimal portfolio and compare portfolio performance using a single index model and z-score. The z-score method is divided into 2 (two) according to the investment strategy, namely growth and value as investors' preferences in choosing a portfolio. The study population uses the IDX BUMN 20 for the period May 2018 - December 2020. The analysis results from the single index method have a portfolio return of 0.001339 with a risk to be faced of 0.0037724. The z-score growth investing method obtains a portfolio return value of 0.000989 and has a risk of 0.023369. Meanwhile, the z-score value investing method has a portfolio return of 0.001614 with a risk of 0.027416. Then the z-score value investing method has the highest performance evaluation value based on the sharpe ratio, treynor measure, and gen's alpha when compared to the other 2 (two) methods.